Popliteal artery pseudoaneurysm of spontaneous occurrence: a case report - Wallace Klein Schwengber; Claudia Carolina Schnorr; Guilherme Camargo Winckler; Ricardo Bocchese Paganella; Marco Aurélio Grudtner (Jornal Vascular Brasileiro, 2024)
Abstract Idiopathic popliteal artery pseudoaneurysms are exceedingly rare, posing significant diagnostic challenges due to their elusive etiology. This report presents the case of a 78-year-old female with no history of trauma or orthopedic procedures who was diagnosed with a large pulsatile mass in the right popliteal fossa. Arteriography confirmed a popliteal artery pseudoaneurysm. Despite extensive clinical evaluation, no causative factors were identified, suggesting an idiopathic diagnosis. The patient underwent open surgical repair using a posterior approach, during which the popliteal artery defect was closed using a bovine pericardium patch. Postoperative follow-up revealed proximal patch stenosis, necessitating angioplasty. This case underscores the need for comprehensive diagnostic evaluation of atypical pseudoaneurysm presentations and highlights the complexities involved in managing idiopathic cases, emphasizing the importance of postoperative follow-up to address potential complications.